2017
DOI: 10.1111/jnu.12346
|View full text |Cite
|
Sign up to set email alerts
|

Health Impact of Climate Change in Older People: An Integrative Review and Implications for Nursing

Abstract: Recognizing the vulnerabilities of older people in the context of climate change is important. Identifying opportunities to promote resilience is an important focus for nurses to develop tailored and targeted nursing interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 44 publications
3
45
0
1
Order By: Relevance
“…Most reviews concluded by calling for more research, noting the limitations observed among the studies included in their reviews, as well as limitations in their reviews themselves. These limitations included, amongst others, some systematic reviews having a small number of publications, 27,28 language restrictions such as including only papers in English, 20,23 arriving at conflicting evidence, 29 difficulty concluding a strong association due to the heterogeneity in methods and measurements or the limited equipment and access to quality data in certain contexts, 27,30–32 and most studies included were conducted in high-income countries. 33,34…”
Section: Resultsmentioning
confidence: 99%
“…Most reviews concluded by calling for more research, noting the limitations observed among the studies included in their reviews, as well as limitations in their reviews themselves. These limitations included, amongst others, some systematic reviews having a small number of publications, 27,28 language restrictions such as including only papers in English, 20,23 arriving at conflicting evidence, 29 difficulty concluding a strong association due to the heterogeneity in methods and measurements or the limited equipment and access to quality data in certain contexts, 27,30–32 and most studies included were conducted in high-income countries. 33,34…”
Section: Resultsmentioning
confidence: 99%
“…• Education for health care professionals on environmental sustainability should include o general knowledge about the climate crisis effects on population health, including 10,11 ▪ air pollution, ▪ exposure to toxins, ▪ heat-related illnesses, 10,11 ▪ extreme weather events, 10,11 ▪ physical and mental health effects of natural disasters, 12 ▪ need for reliable access to clean food and water, and ▪ modification of vector-borne, zoonotic, and waterborne diseases 13 ; o disaster preparedness 10 ; o health system infrastructure resilience [14][15][16][17] ; o supply chain engagement 18 ; o financial, social, and environmental benefits of environmental best practices 19 ; and o real-world examples of environmental best practices in health care services. • Environmentally responsible decision-making in health care delivery should align with local, state and federal regulations and support patient safety and optimal clinical outcomes.…”
Section: Position Statementmentioning
confidence: 99%
“…48 • The health effects of the US health care industry's greenhouse gas emissions are estimated to be equivalent to 470,000 years of healthy life lost (disability-adjusted life years [DALYs]) from pollution-related disease and malnutrition. 43,49 Many multidisciplinary studies exist regarding the health effects of climate change, 17,29,[49][50][51][52][53][54][55][56] as well as the economic and health co-benefits of mitigation, adaptation, and resilience. 32,54,57 A survey of physicians in obstetrics and gynecology found that physicians were more likely than the general public (84% versus 54%) to believe that global warming is real, that portrayal in the media of its seriousness is accurate, and that it is generated by human activities.…”
Section: Rationalementioning
confidence: 99%
“…Furthermore, in 2017, the Lancet Countdown’s highlighted the need to measure how vulnerable people were when they were exposed to climate change over time and investigate the influence of increasing temperatures on existing health problems 9 . In their recent review, Leyva, Beaman and Davidson (2017) reported that most studies on climate change and health have placed a focus on mortality rates related to cardiovascular diseases, while other studies have examined mortality related to respiratory diseases, hospitalization risk and increasing mental health problems 10 . As a consequence, estimates of approximately 1000 additional annual deaths of older people have been proposed due more frequent and intense heat waves for the period of 2036 –2065.…”
Section: Introductionmentioning
confidence: 99%